Antimicrobial effect of different peroxyacetic acid and hydrogen peroxide formats against spores of Clostridium estertheticum. (September 2018) - Mills, John; Horváth, Kylie Marree; Brightwell, Gale
Abstract: "Blown pack" spoilage is primarily caused by Clostridium estertheticum . The primary source of contamination is probably pelts, faeces and soil during opening cuts and de-hiding. Peroxyacetic acid (POAA) based fogs are commonly included in an abattoir's routine cleaning process. Hydrogen peroxide (H2 O2 ) is a powerful oxidizing agent that penetrates microbe cell walls causing cell death. In this study, we compared the ability of H2 O2 and OXYSAN ZS (POAA containing 1-hydroxyethylidine-1, 1-diphosphonic acid as a stabilizer) in different formats to inactivate C. estertheticum spores. Hydrogen peroxide treatment using Phytagel™ gel as carrier was effective on fleece against both naturally contaminating microflora and C. estertheticum spores. This is the first time an antimicrobial treatment has been shown to inactivate C. estertheticum spores on such a complex and highly contaminated matrix. Both H2 O2 and OXYSAN ZS treatments inactivated C. estertheticum spores on stainless steel indicating their potential use as an in-plant decontamination procedure or inclusion in routine in-process cleaning. Highlights: H2 O2 and OXYSAN ZS treatment successfully inactivated C. estertheticum spores on stainless steel. Phytagel™ gel as the carrier for H2 O2 resulted in a significant reduction of C. estertheticum spores when used on fleece. H2 O2 and OXYSAN ZS inactivated C. estertheticum spores on stainless steel indicating potential use as an CIP procedure.